PENENTUAN PORTOFOLIO YANG EFISIEN BAGI CALON INVESTOR PADA INDUSTRI OTOMOTIF DAN KOMPONENNYA YANG TERDAFTAR DI BURSA EFEK SURABAYA - Amaniyah, Evaliati (Fakultas Ekonomi, UIN Maliki Malang, 2007)
This study aimed to determine efficient portofolio for prospective investor in automotive industries and their component that list in Bursa Efek Surabaya in order to decrease risk, by comparing expected return and risk before and after portofolio and choose efficient portofolio among these portofolios. The results of the study revealed that by makingÂ portofolio investor will get more expected return and decrease risk.